Short Dental Implants versus Standard Dental Implants Placed in The Posterior Jaws - Esam Eshaweirf; Abdesalam Sougei (International Journal of Medical Arts, 2023)
Background: Recent studies have revealed that the utilization of shorter dental implants generally represents the optimal approach for addressing the majority of instances involving bone loss in the posterior region of the oral cavity. Short implants have superior performance and exhibit a reduced incidence of complications compared to lengthier implants.Aim of the work: The aim of this study is to conduct a comparative analysis of smaller dental implants and standard dental implants specifically employed in the posterior region of the oral cavity.  Patients and Methods: A research study was conducted at an affiliated dental clinic, focusing on adult patients. The study utilized Biomimetic Ocean implants with internal hex connections manufactured by Avinent Implant System, Spain. Two sizes of implants were used, regular implants measuring 10 mm and short implants measuring 7 mm. The sample size was 60 Patients. A total of 29 standard implants and 17 short implants were put. The methods involved comprehensive ethical considerations, obtaining informed consent from participants, and thorough examinations at multiple time points. Surgical and prosthetic procedures were performed, and clinical examinations, radiographic measurements, and stability assessments were conducted. Statistical analysis was employed to analyze the collected data.Results: The results indicate that all of the implants in both groups were effective. Following the surgical procedure, it was observed that the Standard Implants Group exhibited a comparatively higher mean initial stability quotient [ISQ] score of 77.1 ± 65, whereas the Short Implants Group displayed a mean ISQ score of 71.7 ± 81. This discrepancy in ISQ values between the two groups during the visit is noteworthy. Both groups had comparable mean ISQ values during the subsequent surgical procedure.Conclusion: The findings of this study indicate that shorter implants demonstrate comparable efficacy and stability to lengthier implants in those experiencing jawbone loss.